Penerapan Undang-Undang Perlindungan Nelayan Terhadap Masyarakat Nelayan Di Provinsi Jawa Tengah - Rezky Arianti Salim; Nurjannah Abdullah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The protection of fishermen is based on Undang-Undang Nomor 7 Tahun 2016 with a research focus on the efforts made by the government to ensure the protection of fishing communities in Central Java. This research uses a qualitative-descriptive research type with data collection techniques using library research methods. Therefore, the type of data in this research is secondary data. The results of the research then contain the government's way of ensuring the protection of fishermen through the Fishermen's Insurance Premium Assistance program by the Ministry of Maritime Affairs and Fisheries. During the implementation of the program from 2016 to 2019, 111,547 small fishermen received insurance assistance from the government. The Central Java Provincial Government also provides a fishermen's insurance program through the Central Java Maritime and Fisheries Agency to provide wider opportunities for fishermen in Central Java to have insurance. In its implementation, the provision of fishermen's insurance has several obstacles, such as a limited budget and the fact that many fishermen are reluctant to register for insurance independently. Therefore, not all Central Java fishermen have this fishermen insurance. However, there have been fishermen who have felt the benefits of fishermen's insurance and began to realize that insurance is important to have. This study concludes that the implementation of the fishermen's insurance program can be said to be successful, but the implementation has not been optimal.